Weeds in pastures: a phytosociological approach in Ceara areas - Silva, Josefa Maria Francieli da; Sarmento, Hercules Gustavo Santos; Araújo, Hellen Thayse Nascimento; Oliveira, Alexandre Bosco de; Oliveira, Lamartine Soares Cardoso de (Agrarian, 2019)
The aim of this study was to study the phytosociology of weed species in areas of pasture cultivated with Brachiaria decumbens and Cynodon sp. (Tifton 85), in Ceará State, Brazil. The square inventory methodology was used in order to assess the weed community. Weed samples were quantified and classified by family, genus and species, using books and classification keys. The classification and quantification data of species allowed to calculate the following phytosociological variables: frequency (F), relative frequency (Fr), density (D), relative density (Dr), absolute dominance (DoA), relative dominance (DoR), importance value index (IVI), and similarity index (IS). The Amaranthaceae family was the one with the greatest intensity of species in both areas, represented mainly by Alternanthera tenera colla and Amaranthus viridis. In the area cultivated with B. decumbens, Cyperus rotundus presented higher results for frequency, density and abundance. In the Tifton 85 area, Nicandra physalodes presented higher values of density and abundance. The similarity of weed populations in pasture areas was 42.11%, with four species common to both areas.